Binder for wood-based panels comprising amino acid polymer and polyaldehyde compound
By using a binder composition of an amino acid polymer with primary amino groups and a polyaldehyde compound, the problem of difficulty in effectively utilizing non-petrochemical resources and reducing emissions of harmful substances in the prior art is solved, and the lignocellulose composite material is realized Improved intensity and improved productivity.
Patent Information
- Application Number
- CN202380048397.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, when producing multi-layer or single-layer lignocellulose composite materials, it is difficult to effectively utilize non-petrochemical resources as the binder component, and there are problems with the emission of potentially harmful substances.
Using a binder composition comprising an amino acid polymer having two or more primary amino groups, such as polylysine, and polyaldehyde compound, the binder is hardened by the reaction of these components, This produces lignocellulosic composite materials that increase strength and reduce emissions of harmful substances.
The strength improvement of lignocellulose composites and the reduction of harmful substances in the production process are achieved, especially when compared with traditional methods, which shortens heating and pressing time and reduces material expansion.
Smart Images

Figure BDA0005197849180000291 
Figure BDA0005197849180000321 
Figure BDA0005197849180000341
Abstract
Description
[0001] The present invention relates to a method for producing a lignocellulose composite material, a binder composition suitable for the method, and a lignocellulose composite material that can be produced by the method of the present invention. The present invention further relates to the use of the lignocellulose composite material. In addition, the present invention relates to a kit for producing a binder composition according to the present invention, the binder composition is used to produce a lignocellulose composite material, and to the corresponding use of such a binder composition.
[0002] Typically, in a method for producing a multilayer or monolayer lignocellulosic composite, a mixture of lignocellulosic particles (i.e. particles consisting essentially of lignocellulose) and a binder is provided or prepared. The mixture is typically dispersed, for example to obtain the first layer of a multilayer mat or to obtain a monolayer mat. When producing a multilayer composite, two or more mixtures of lignocellulosic particles are dispersed in sequence to obtain a mat having two or more individual layers. The resulting mat is then compacted, and during or after compaction, the compacted mat or mixture is hardened, i.e. the mixture is treated in such a way that the binder undergoes a hardening process.
[0003] There is an industrial need for an improved process for producing multi-layer or single-layer lignocellulosic composites, in which binder components can be used which can be obtained to the greatest possible extent from non-petrochemical resources, preferably from renewable resources, and which are suitable for reducing or avoiding potentially harmful substances, like formaldehyde and isocyanates or substances that release formaldehyde, like for example N-methylol compounds, during or after the production process of the composite materials.
[0004] The following documents relate to certain aspects of the method for producing multi-layer or single-layer lignocellulosic composite materials:
[0005] Document US 2011 / 0262648 A1 describes durable thermosets from reducing sugars and primary polyamines.
[0006] Document WO 2015 / 177114 A1 relates to a pre-reacted binder composition based on water-soluble carbohydrate-polyamino acids.
[0007] Document EP 3 611 225 A2 relates to binder compositions comprising polylysine and at least one reducing sugar, wherein the at least one reducing sugar is not a polyaldehyde in the sense as defined herein, to articles and to a process for the manufacture of the articles.
[0008] Document WO 2022 / 008671 A1 describes a resin-impregnated fiber material in the form of a sheet or a web comprising an impregnating resin, wherein the impregnating resin comprises a combination of a resin component A and a resin component B, wherein the resin component A may be an aminoplast resin (i.e., a condensation product of one or more amino compounds - excluding amino acids - and one or more aldehydes), and the resin component B is an oligomer or polymer having ethylenically unsaturated double bonds.
[0009] In view of the existing prior art, there is still a need for improved methods for producing multi-layer or single-layer lignocellulosic composites, in which binder components obtainable from non-petrochemical resources, preferably from renewable resources, are used as much as possible, and in which harmful or potentially harmful substances are reduced or avoided as much as possible.
[0010] Accordingly, the main object of the present invention is to provide an improved method for producing a multi-layer or single-layer lignocellulosic composite material, in particular such a method, wherein the resulting lignocellulosic composite material has increased strength when compared to a similar lignocellulosic composite material not produced by the method according to the present invention, or wherein shorter heating and / or pressing times are required to obtain a lignocellulosic composite material having a strength comparable to that of a similar lignocellulosic composite material not produced by the method according to the present invention.
[0011] Another object of the present invention is to provide a binder composition suitable for use in an improved process for producing a multi-layer or single-layer lignocellulosic composite material, and a lignocellulosic composite material produced by said process.
[0012] Yet another object of the present invention is to provide a method for producing a multi-layer or single-layer lignocellulosic composite material and a corresponding binder composition, wherein the binder composition will contain a certain proportion of bio-based components, which proportion should be as high as possible in order to reduce or avoid the emission of harmful or otherwise undesirable volatile compounds during or after production and to allow safe disposal and / or reduce potentially environmentally harmful waste.
[0013] It has now been found that the main object and other objects of the present invention can be achieved by a method for producing a lignocellulose composite material comprising one (particularly a "single-layer lignocellulose composite material") or a plurality of lignocellulose composite layers (particularly a "multi-layer lignocellulose composite material"), the method comprising at least the following steps:
[0014] S1) providing or preparing a mixture comprising at least:
[0015] -Lignocellulosic particles
[0016] as well as
[0017] - a binder composition (preferably an aqueous binder composition, ie a binder composition comprising water) comprising at least the following as components preferably for hardening the binder or binder composition:
[0018] c1) one or more amino acid polymers having two or more primary amino groups, preferably comprising one or more polylysine, and
[0019] c2) one or more polyaldehyde compounds, preferably selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups;
[0020] S2) compacting the mixture from step S1) to obtain a compacted mixture,
[0021] as well as
[0022] S3) applying heat and optionally pressure (preferably applying heat and pressure) to the compacted mixture from step S2) so that the binder of the binder composition (preferably the binder or a curable component of the binder composition) hardens and produces a lignocellulosic composite material (or multiple lignocellulosic composite layers).
[0023] The invention as well as preferred variations and preferred combinations of its parameters, features and elements are defined in the appended claims. Preferred aspects, details, modifications and advantages of the invention are also defined and explained in the following description and in the examples shown below.
[0024] It has now been found (and is shown in the following examples) that the method for producing a multilayer or single-layer lignocellulosic composite material according to the present invention as described herein shows certain improvements over similar methods known from the prior art. In particular, the method according to the present invention produces a lignocellulosic composite material with increased strength (increased internal bonding strength) when compared to a similar lignocellulosic composite material not produced according to the method of the present invention, or wherein a shorter heating and / or pressing time is required to obtain a lignocellulosic composite material with a strength comparable to that of a similar lignocellulosic composite material not produced according to the method of the present invention. In many cases, the method according to the present invention also produces a lignocellulosic composite material that shows less swelling when in contact with moisture when compared to a similar lignocellulosic composite material not produced according to the method of the present invention.
[0025] If not stated otherwise, preferred embodiments, aspects or features of the invention may be combined with other embodiments, aspects or features, in particular with other preferred embodiments, aspects or features, regardless of the category to which the embodiments, aspects or features relate. A combination of a preferred embodiment, aspect or feature with other preferred embodiments, aspects or features in each case again results in a preferred embodiment, aspect or feature.
[0026] As used herein, the term "lignocellulose particles" refers to and includes lignocellulose particles of any type, size and shape, such as fiber, debris, strand, flake, sawmill shavings and sawdust or its mixture. In addition, any type of lignocellulose biomass such as birch, beech, alder, pine, spruce, larch, eucalyptus, basswood, poplar, ash, fir, tropical wood, sisal, jute, flax, coconut, kenaf, hemp, banana, straw, cotton stalk, bamboo etc. can be used as the source of the lignocellulose particles. Lignocellulose particles from both primary wood and / or waste wood (such as old furniture) can be used to produce lignocellulose composite materials of the present invention. According to the present invention, a mixture of different types of lignocellulose particles can be used in the production of lignocellulose composite materials.
[0027] As used herein, the term "single-layer lignocellulosic composite" (i.e., a lignocellulosic composite comprising one lignocellulosic composite layer) designates and includes any single-layer composite material containing lignocellulosic particles and a hardened binder that binds the lignocellulosic particles. In addition, the term "single-layer" designates that the lignocellulosic composite material comprises only one layer of lignocellulosic material and a binder, wherein the single-layer is preferably produced by a method comprising a single step of dispersing the lignocellulosic particles. The "single-layer lignocellulosic composite" can have any shape, such as a rectangle, a square, a circle, a triangle, etc. The "single-layer lignocellulosic composite" can also have any thickness, density and color, as long as it contains lignocellulosic particles and a hardened binder. The "single-layer lignocellulosic composite" can also contain several other compounds that are different from the lignocellulosic particles and the binder. The lignocellulosic particles used to produce the "single-layer lignocellulosic composite" are lignocellulosic biomass of the same type or different types (preferred types are described above).
[0028] As used herein, the term "multilayer lignocellulosic composite material" (i.e., a lignocellulosic composite material comprising more than one lignocellulosic composite material layer) designates and includes any multilayer composite material containing lignocellulosic particles and a hardened binder for bonding the lignocellulosic particles, and wherein distinguishable (individual) layers are present in the composite material. The multilayer lignocellulosic composite material preferably comprises at least two distinguishable (individual) layers in the same composite material, in particular a core layer and an upper and lower surface layer; or four or more layers. Adjacent layers of the multilayer lignocellulosic composite material are distinguishable in terms of their composition, density, color or any other characteristic, and the adjacent layers contain the same type of lignocellulosic particles and / or binder or different types of lignocellulosic particles and / or binder. These (individual) layers may also contain or consist of the following materials different from the lignocellulosic particles and / or binder: such as plastics, fabrics, paint coatings, etc., for example foreign matter derived from waste wood, however, at least one layer of the "multilayer lignocellulosic composite material" must contain lignocellulosic particles. The lignocellulosic particles used to produce the individual layers of the "multilayer lignocellulosic composite material" are lignocellulosic biomass of the same type or different types (preferred types see above). The lignocellulosic particles used to produce the separate / individual layers of the "multi-layer lignocellulosic composite" are of the same or different type of lignocellulosic biomass (preferred types see above) or of the same or different mixtures of two or more such types of lignocellulosic biomass. Furthermore, the term "multi-layer" specifies that the lignocellulosic composite comprises at least two separate layers, wherein at least one, preferably two or more of these separate layers comprise lignocellulosic material and a binder, wherein one or more or all of the layers are preferably produced in a multi-step process which, for each (separate) layer of lignocellulosic material and binder, comprises a step of dispersing the lignocellulosic particles.
[0029] As used herein, the term "one or more amino acid polymers having two or more primary amino groups" (component c1) of the binder composition) designates a polymer compound which is a polymerization product of an amino acid and optionally other monomers (wherein the monomers of the polymer compound are preferably linked or bound to each other via an amide bond), wherein the other monomers are selected from the group consisting of:
[0030] a) an amine comprising at least two amino groups, wherein the amines are not amino acids, and
[0031] b) organic compounds having at least two carboxyl groups, preferably selected from the group consisting of organic dicarboxylic acids and organic tricarboxylic acids, wherein these organic compounds having at least two carboxyl groups are not amino acids,
[0032] Wherein, preferably at least 50 wt.-%, preferably at least 75 wt.-%, preferably at least 85 wt.-%, preferably at least 90 wt.-%, preferably at least 95 wt.-%, preferably at least 97.5 wt.-%, preferably at least 99 wt.-%, preferably 100 wt.-% amino acids are used as monomers for the polymerization reaction, based on the total amount of monomers to form one or more amino acid polymers having two or more primary amino groups.
[0033] Typically and for the purposes of the present invention, the one or more amino acid polymers having two or more primary amino groups may include or consist of dimers (n=2), trimers (n=3), oligomers (n=4-10) and / or macromolecules (n>10), where n is the number of monomers that have reacted to form the dimer, trimer, oligomer and macromolecule of the one or more amino acid polymers having two or more primary amino groups.
[0034] One skilled in the art will select monomers for producing the amino acid polymer(s) having two or more primary amino groups so as to obtain the desired amino acid polymer(s) having two or more primary amino groups.
[0035] As used herein, the term "one or more amino acid polymers having two or more primary amino groups" also includes derivatives obtained by modifying the one or more amino acid polymers having two or more primary amino groups after polymer synthesis. The modification can be carried out by reacting with the following reagents:
[0036] i) alkyl or alkenyl carboxylic acids such as, for example, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, hexadecenoic acid, stearic acid, oleic acid, linoleic acid and / or linolenic acid and / or Li, Na, K, Cs, Ca or ammonium salts thereof, and / or
[0037] ii) polyalkylene oxides terminated by amino groups and / or acid groups and having one, two or more functionalities, preferably polyethylene oxide, polypropylene oxide and / or polyethylene oxide-propylene oxide, and / or
[0038] iii) alkylene oxides, such as ethylene oxide, propylene oxide and / or butylene oxide, and / or
[0039] iv) lactones, such as ε-caprolactone, δ-valerolactone, γ-butyrolactone, and / or
[0040] v) Alcohols, such as alkanols, for example oleyl alcohol.
[0041] One or more amino acids that can be present as monomers in one or more amino acid polymers with two or more primary amino groups are organic compounds comprising at least one primary amine (-NH2) functional group and at least one carboxyl (-COOH) functional group. The one or more amino acids are preferably selected from the group consisting of: lysine, histidine, isoleucine, leucine, methionine, phenylalanine, threonine, tryptophan, valine, arginine, aspartic acid, glutamic acid, serine, asparagine, glutamine, cysteine, selenocysteine, glycine, α-alanine, β-alanine, tyrosine, γ-aminobutyric acid, ε-aminocaproic acid, ornithine, diaminopimelic acid, 2,3-diaminopropionic acid, 2,4-diaminobutyric acid or its mixture. Amino acid can be used in its L- or D- or racemic form. Amino acid can also be used in its cyclic lactam form, such as ε-caprolactam.
[0042] Preferred amino acids for the polymerization reaction (used in the method according to the invention as monomers for forming the one or more amino acid polymers having two or more primary amino groups) are diamino acids comprising two amino groups, preferably two primary amino groups (-NH2) and at least one carboxyl group (-COOH). Such diamino acids are preferably selected from the group consisting of ornithine, diaminopimelic acid, 2,3-diaminopropionic acid, 2,4-diaminobutyric acid and lysine. Lysine is preferred as an amino acid monomer for forming the one or more amino acid polymers having two or more primary amino groups. For this purpose, L-lysine is even more preferred.
[0043] Also preferred is the process of the invention as described herein (or as described herein as a preferred process of the invention), wherein the one or more amino acid polymers having two or more primary amino groups (component c1)) comprises or is a polymer compound which is the polymerization product of: an amino acid,
[0044] Preferably a diamino acid comprising two primary amino groups (-NH2) and at least one carboxyl group (-COOH),
[0045] More preferably, it is an amino acid selected from the group consisting of ornithine, diaminopimelic acid, 2,3-diaminopropionic acid, 2,4-diaminobutyric acid and lysine.
[0046] The one or more amino acid polymers having two or more primary amine groups may be linear or branched or partially linear and partially branched.
[0047] For purposes of the present invention, preferred amino acid polymer(s) having two or more primary amine groups are described below.
[0048] As used herein, the term "polyaldehyde compound" (component c2 of the binder composition) is designated as a compound having two or more (and preferably two) aldehyde groups and a compound having a tautomer containing two or more (and preferably two) aldehyde groups (such as 5-(hydroxymethyl) furan-2-carboxaldehyde), which can react with an amine compound, and optionally another compound to form a hardened binder. As used herein, the phrase "a compound having a tautomer containing two or more aldehyde groups" means a compound that can provide two or more aldehyde groups in a suitable reaction (e.g., in a reaction with one or more amino acid polymers having two or more primary amino groups), although the "compound having a tautomer containing two or more aldehyde groups" may exist in a tautomeric form of its chemical structure that does not show (or reveal) one or two aldehyde functional groups (this phenomenon is also called "keto-enol tautomerism"). An example of such a tautomeric form of a compound having a tautomer containing two or more aldehyde groups, wherein the tautomeric form does not show two available aldehyde functionalities of the compound, is 5-(hydroxymethyl)furan-2-carbaldehyde (HMF; CAS RN 67-47-0).
[0049] In order to be used in component c2) in the binder composition, such one or more polyaldehyde compounds must be capable of reacting with the amino acid polymer having two or more primary amino groups used in component c1).
[0050] The binder composition used in the method of the present invention comprises component c1) one or more amino acid polymers having two or more primary amino groups, and c2) one or more polyaldehyde compounds as components preferably used for hardening the binder or binder composition. Components c1) and c2) are also referred to herein as "curable components", preferably as "heat-curable components" of the binder or binder composition. More specifically, components c1) and c2) are also collectively referred to herein as "binders", and individually referred to as "curable components", preferably "heat-curable components" of the binder.
[0051] Preferred is the method of the invention as described herein (or as described herein as preferred method of the invention), wherein the one or more amino acid polymers of component c1) of the binder composition comprise (or are) one or more polylysines,
[0052] Preferably, the one or more polylysine
[0053] - having a weight average molecular weight M of ≥800 g / mol, preferably ≥1000 g / mol, more preferably ≥1150 g / mol, even more preferably ≥1500 g / mol w , wherein preferably the weight average molecular weight Mw was determined by size exclusion chromatography;
[0054] and / or
[0055] - having a weight average molecular weight M of ≤10000 g / mol, preferably ≤8000 g / mol, more preferably ≤5000 g / mol, and still more preferably ≤4000 g / mol w , wherein preferably the weight average molecular weight M w was determined by size exclusion chromatography;
[0056] and / or
[0057] -With a temperature of 800g / mol≤M w ≤10000 g / mol, preferably 1000 g / mol≤M w ≤8000g / mol, more preferably 1500g / mol≤M w ≤5000 g / mol, and still more preferably 1800 g / mol≤M w Weight average molecular weight M within the range of ≤4000g / mol w , wherein preferably the weight average molecular weight M w was determined by size exclusion chromatography;
[0058] and / or
[0059] - comprises at least 85 wt.-%, preferably at least 95 wt.-%, more preferably at least 99 wt.-% and yet even more preferably 100 wt.-% of lysine monomers as monomers integrated in its polymer structure, based on the total weight of the polylysine-forming monomers.
[0060] Preferably, the wt.-% proportion (percent by weight) of lysine (monomer), preferably L-lysine, in the one or more polylysines can be determined in a manner known per se, for example by complete hydrolysis of the polylysine and subsequent analysis of the resulting monomers by HPLC / MS. In this formal calculation for the amino acid (lysine) polymers of component c1), as preferably prepared by condensation of lysine, the water released from the amino acid in the condensation is neglected.
[0061] The weight average molecular weight M of one or more amino acid polymers having two or more primary amino groups (such as used in the binder composition according to the method of the present invention) (including polylysine) is w Preferably it is determined by size exclusion chromatography (SEC) as generally known in the art, and preferably under conditions and applying technical parameters as specified in the Examples section herein (see method No. 7 as described in the Examples section).
[0062] The one or more polylysines may be linear or branched or partially linear and partially branched.
[0063] As used herein, the term "polylysine(s)" designates the polymerization product of the monomeric lysine, preferably L-lysine, and optionally additional monomers selected from the group consisting of:
[0064] a) amino acids,
[0065] b) amines comprising at least two amino groups, wherein these amines are not amino acids,
[0066] as well as
[0067] c) dicarboxylic acids which are not amino acids and tricarboxylic acids which are not amino acids,
[0068] The proportion (in wt.%) of lysine preferably used as monomer for the polymerization reaction to produce polylysine is ≥ 10 wt.%, preferably ≥ 20 wt.%, based on the total amount of monomers used for the polymerization of polylysine.
[0069] or
[0070] At least 50 wt.-%, preferably at least 75 wt.-%, preferably at least 85 wt.-%, preferably at least 95 wt.-%, more preferably at least 99 wt.-% and yet even more preferably 100 wt.-% of lysine, based on the total amount of monomers used, is used as monomer for the polymerization reaction to produce the polylysine.
[0071] Preferred for the purposes of the present invention as one or more polylysines are homopolymers of lysine, preferably homopolymers of L-lysine.
[0072] Typically and for the purposes of the present invention, polylysine may include or consist of dimers (n=2), trimers (n=3), oligomers (n=4-10) and / or macromolecules (n>10), where n is the number of lysine monomers that have reacted to form one or more dimers, trimers, oligomers and macromolecules of polylysine. In addition, lysine monomers may be present in a limited amount in a mixture with polylysine, for example due to incomplete conversion of monomers during the polymerization reaction to produce polylysine.
[0073] Lysine has two possibilities for reaction during polymerization. Either α-NH2 or ε-NH2 can react with carboxylic acids. Thus, there are two types of linear polylysine, namely α-polylysine or ε-polylysine. Polymerization can also be carried out in a way that both α-NH2 and ε-NH2 react with carboxylic acid groups to form both α-linkages and ε-linkages. Preferably, the polylysine is a branched polylysine. The preferred polylysine or polylysines as used according to the present invention have more ε-linkages than α-linkages. Preferably, the ratio of ε-linkages to α-linkages is between 1.0:1 and 6.0:1, preferably between 1.25:1 and 4.0:1, preferably between 1.5:1 and 3.0:1. This ratio can be adjusted by adjusting the ratio of the polylysine to the α-linkages. 1 The corresponding signal in the H-NMR spectrum was integrated to determine it.
[0074] In the present context, the term polylysine preferably also includes polylysine derivatives which are or can be prepared by: (i) modification reaction of amino groups present in polylysine obtained by polymer synthesis with (ii) electrophiles like carboxylic acids, epoxides and lactones, wherein the total amount of amino groups reacted in the modification reaction is 20% or less, preferably 10% or less, based on the total amount of amino groups in the polylysine obtained in the polymer synthesis (i.e. before modification).
[0075] In our experiments it has been found that the method according to the invention wherein the binder composition comprises as component c1) an amino acid polymer having two or more primary amino groups (in particular one or more polylysines) is suitable for producing a lignocellulose composite material which exhibits increased strength (or requires a shorter pressing time to achieve a similar strength) when compared to similar lignocellulose composite materials in which other amino-functionalized compounds are used in the binder composition. For example, it is reported in WO 2015 / 177114 A1 that a binder composition comprising a lysine monomer and hexamethylenediamine (HMDA) as an amino-functionalized component does not harden satisfactorily in the presence of reducing sugars and sodium hydroxide.
[0076] Also preferred is the process of the invention as described herein (or as described herein as a preferred process of the invention), wherein the binder composition is one or at least one of the plurality of polyaldehyde compounds of component c2), or all of the plurality of polyaldehyde compounds, selected from the group consisting of oxidized starch, glyoxal, dialdehyde cellulose, malondialdehyde, succindialdehyde, glutaraldehyde, adipaldehyde, furan-2,5-dicarboxaldehyde, 5-(hydroxymethyl)furan-2-carboxaldehyde (HMF; CAS RN 67-47-0), 3-hydroxy-2-oxo-propionaldehyde, and mixtures thereof.
[0077] As mentioned above, 5-(hydroxymethyl)furan-2-carbaldehyde (HMF) is considered to be a compound having two aldehyde groups for the purposes of this specification because it has an enol-keto tautomer containing two aldehyde groups.
[0078] Preferably, one or at least one of the plurality of polyaldehyde compounds of component c2) of the binder composition, or all of the plurality of polyaldehyde compounds (for the purposes of the process of the invention as described herein or as described herein as a preferred process of the invention) are selected from the group consisting of glyoxal, furan-2,5-dicarboxaldehyde, 5-(hydroxymethyl)furan-2-carboxaldehyde, and mixtures thereof.
[0079] More preferably, one or at least one of the plurality of polyaldehyde compounds is 5-(hydroxymethyl)furan-2-carbaldehyde.
[0080] In addition, preferred is the method of the present invention as described herein (or as described herein as a preferred method of the present invention), wherein the mixture provided or prepared in step S1) further comprises c3) one or more α-hydroxycarbonyl compounds, preferably selected from the group consisting of: glycoaldehyde, glyceraldehyde, 1,3-dihydroxyacetone, hydroxyacetone, arabinose, xylose, glucose, mannose, fructose, sucrose, and mixtures thereof.
[0081] In our experiments it has been found that the method according to the invention, in which the binder composition used in step S1) comprises one or more polyaldehyde compounds (selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups), in particular one or more polyaldehyde compounds as specified above as preferred, as component c2), is suitable for producing lignocellulosic composites showing increased strength (or requiring shorter pressing times to achieve similar strength) and / or showing less swelling upon contact with moisture, when compared to similar lignocellulosic composites from the prior art in which reducing sugars are used in the binder composition but no polyaldehyde compounds (see, for example, EP 3 611 225 A2).
[0082] Also preferred is the process of the invention as described herein (or as described herein as a preferred process of the invention), wherein the ratio of (i) the total weight of the one or more amino acid polymers of the binder composition being component c1) : (ii) the total weight of the one or more polyaldehyde compounds of the binder composition being component c2) is in the range of 60:40 to 95:5, preferably 65:35 to 90:10, and more preferably 70:30 to 90:10.
[0083] Also preferred is the process of the invention as described herein (or as described herein as preferred process of the invention), wherein the molar ratio of (i) primary amino groups provided by the one or more amino acid polymers of the binder composition being component c1):(ii) aldehyde groups provided by the one or more polyaldehyde compounds of the binder composition being component c2) is in the range of 0.1 to 1.2, preferably 0.2 to 1.0, and more preferably 0.3 to 0.8. Again, for the purposes of this specification, 5-(hydroxymethyl)furan-2-carbaldehyde (HMF) is considered to be a compound having two aldehyde groups.
[0084] In our experiments it has been found that particularly high internal bond strengths can be achieved in the lignocellulosic composites produced by the method according to the invention when 5-(hydroxymethyl)furan-2-carboxaldehyde is used as the polyaldehyde (i.e. tautomeric dialdehyde) compound of component c2), or shorter pressing times are required to achieve a defined internal bond strength when compared to the use of a similar binder in which another carbonyl compound is used instead of a polyaldehyde. Particularly good results (in terms of internal bond strength and / or reduced pressing times) are achieved in the method according to the invention when one or more polylysines are used as component c1) of the binder composition and 5-(hydroxymethyl)furan-2-carboxaldehyde is used as component c2) of the binder composition.
[0085] Similarly, in our experiments it has been found that the best practical results are achieved for lignocellulosic composites produced by the method according to the invention when the ratio of (i) the total weight of one or more amino acid polymers of the binder composition as component c1): (ii) the total weight of one or more polyaldehyde compounds of the binder composition as component c2) is selected within the preferred range outlined above.
[0086] In our experiments it has been found that the best practical results are achieved for the lignocellulosic composite materials produced by the process according to the invention when the binder composition has components c1) and / or c2) in the above defined proportions.
[0087] Furthermore, preferred is the method of the invention as described herein (or as described herein as a preferred method of the invention), wherein the mixture (and preferably the binder composition) provided or prepared in step S1) of the method further comprises a carrier liquid, preferably water, wherein preferably
[0088] - component c1) one or more amino acid polymers are present in the binder composition in a total amount ranging from ≥ 20 wt.-% to ≤ 50 wt.-%, preferably from ≥ 25 wt.-% to ≤ 45 wt.-%, and more preferably from ≥ 25 wt.-% to ≤ 40 wt.-%, relative to the total weight of components c1) to c2) and the carrier liquid;
[0089] and / or
[0090] - component c2) one or more polyaldehyde compounds are present in the binder composition in a total amount in the range of ≥3 wt.-% to ≤20 wt.-%, preferably ≥5 wt.-% to ≤15 wt.-%, and more preferably ≥7 wt.-% to ≤12 wt.-%, relative to the total weight of components c1) to c2) and the carrier liquid;
[0091] and / or
[0092] The pH value of the binder composition is in the range of 10 to 14, preferably 11 to 14, more preferably 12 to 14.
[0093] As regards the amounts of components c1) and c2) and c3), according to the invention, these components are not mandatory to be present in the ideally mixed binder composition. Instead, the individual components can be applied individually to the lignocellulosic particles and the amounts of the components are given relative to the total amount of the individual components as present in the final binder composition or prepared to give the final binder composition.
[0094] Also preferred is a method according to the invention as described herein (or as described herein as a preferred method of the invention), wherein in the mixture provided or prepared in step S1) of the method,
[0095] The total amount of component c1) of the binder composition, one or more amino acid polymers, and component c2) of the binder composition, one or more polyaldehyde compounds
[0096] The binder composition is present in (or used for the preparation of) the binder composition in a range of ≥3 wt.-% to ≤8 wt.-%, preferably ≥3.5 wt.-% to ≤7.5 wt.-%, and more preferably ≥4 wt.-% to ≤6.5 wt.-%, relative to the total amount of lignocellulosic particles in the mixture in the oven-dried state.
[0097] Surprisingly, with relatively low total amounts of components c1) and c2) as specified above, sufficiently stable and strong lignocellulosic composites can be obtained for use as lignocellulosic composite boards in many applications, for example in the furniture industry.
[0098] Typically, in step S1) for preparing the mixture, the lignocellulosic particles may be blended with one or more or all components of the binder composition, and / or one or more or all components of the binder composition may be sprayed onto the lignocellulosic particles, whereas prior to blending or spraying, the components of the binder composition are premixed or not (preferably, they are premixed).
[0099] The process of the invention as described herein (or as described herein as a preferred process of the invention) is preferred, wherein the mixture in step S1) is prepared by providing or preparing in a first step S1-1) a binder composition comprising at least components c1) and c2) and preferably water, and in a second step S1-2), contacting the binder composition provided or prepared in step S1-1) with lignocellulosic particles, preferably spraying the binder composition onto the lignocellulosic particles.
[0100] In the method of the present invention, the binder composition may further comprise one, two or more compounds independently selected from the group consisting of alkali metal salts and alkaline earth metal salts (preferably sodium nitrate), hydrophobic agents (preferably paraffin and mixtures containing paraffin, more preferably paraffin emulsions), dyes, pigments, antifungal agents, antibacterial agents, rheology modifiers, fillers, release agents, surfactants and tensides.
[0101] Preferred is the method of the present invention (preferably, as defined herein above as preferred), wherein the method for producing the lignocellulosic composite material comprises steps that are carried out batchwise and / or steps that are carried out continuously. Therefore, the method of the present invention is suitable for a wide variety of different production facilities and provides a variety of options for producing the desired lignocellulosic composite material, i.e. a multilayer lignocellulosic composite material or a single-layer lignocellulosic composite material comprising one or more, preferably two or more, more preferably three lignocellulosic composite material layers. As a preferred method of the present invention, batch production is selected to produce individual lignocellulosic composite materials, for example with different shapes, thicknesses, etc., while a fully continuous method is preferably selected for the production of more uniform lignocellulosic composite materials, for example with similar shapes, thicknesses, etc.
[0102] The preferred method of the present invention can also and preferably comprises one or more steps carried out in batches, and one or more steps carried out continuously. A preferred example of such a combined method is to produce a single-layer lignocellulose composite material in a method step carried out continuously, and then use the continuously produced single-layer lignocellulose composite material as a starting material (e.g. as the core layer of the multi-layer lignocellulose composite material) to produce a multi-layer lignocellulose composite material in batches (and preferably separately).
[0103] It is also preferred that the process of the invention as described herein (or as described herein as a preferred process of the invention) wherein the lignocellulosic composite material is a lignocellulosic board selected from the group consisting of:
[0104] - High-density fiberboard (HDF);
[0105] - Medium density fiberboard (MDF);
[0106] - Low-density fiberboard (LDF);
[0107] - wood fiber insulation boards;
[0108] - Oriented Strand Board (OSB);
[0109] - particleboard; and
[0110] - natural fiberboard, preferably with fibers from the group consisting of sisal, jute, flax, coconut, kenaf, hemp, banana and mixtures thereof;
[0111] The wood cellulose board is
[0112] - single-layer wood cellulose board, or
[0113] -Multi-layer wood cellulose board,
[0114] A multi-layer lignocellulosic board having a core layer and having an upper surface layer and a lower surface layer is preferred.
[0115] Furthermore, preferred according to the invention are multilayer panels with different compositions in the individual layers, and also multilayer panels with different binder compositions in the individual layers. Preferred variants are three-layer panels with urea-formaldehyde and / or isocyanate in the core layer and with the binder composition of the invention in the surface layers.
[0116] According to a preferred aspect of the method of the invention, the production method produces a lignocellulosic composite material, i.e. preferably a single-layer lignocellulosic board or a multi-layer lignocellulosic board, more preferably a multi-layer lignocellulosic board. The multi-layer lignocellulosic board is more preferably a board having at least a core layer and an upper surface layer and a lower surface layer. The total number of layers is then three or more. If the number of layers is four or more, one or more intermediate layers are present. Preferred is a three-layer board having a core layer, an upper surface layer and a lower surface layer.
[0117] Therefore, a preferred aspect of the present invention relates to a method for producing high density fiberboard (HDF), medium density fiberboard (MDF), low density fiberboard (LDF), wood fiber insulation board, oriented strand board (OSB), particleboard or natural fiberboard, wherein the board is preferably a single-layer lignocellulosic board or a multi-layer lignocellulosic board, more preferably a multi-layer lignocellulosic board, most preferably a three-layer lignocellulosic board.
[0118] The compaction in step S2) is usually carried out at a pressure of 0.1 to 3.0 MPa, preferably 0.2 to 2.5 MPa, more preferably 0.3 to 2.0 MPa. Typically, in step S2), the mixture from step S1) is compacted without applying heat to the mixture. Optionally, during or after step S2) and before method step S3), energy can be introduced into the compacted mixture with one or more energy sources of any kind by a preheating step. Suitable energy sources are, for example, hot air, electrical energy (such as microwave or high frequency heating), steam or a steam / air mixture. This increases the temperature of the compacted mixture and can change its moisture. After the optional preheating step, the temperature in the core of the compacted mixture can be between 40°C and 80°C, preferably between 40°C and 70°C. Preheating with steam and a steam / air mixture can also be carried out in a manner that only the area near the surface is heated without heating the core.
[0119] The compaction in step S2) and optionally the preheating during or after step S2) can be carried out by methods known to the person skilled in the art, such as those described in M. Dunky, P. Niemz, Holzwerkstoffe and Leime [Wood Materials and Glues], Springer Verlag Heidelberg, 2002, pp. 122 and 819 or in H.-J. Deppe, K. Ernst, MDF—Medium Density Fiberboard, DRW-Verlag, 1996, pp. 44, 45 and 93 or in A. Wagenfuhr, F. Scholz, Taschenbuch der Holztechnik [Handbook of Wood Technology], Fachbuchverlag Leipzig, 2012, p. 219.
[0120] In step S3) of the method of the present invention, heat and / or (preferably "and") pressure are applied to the compacted mixture from step S2) so that the binder of the binder composition hardens.
[0121] The heat is applied in such a way that during or at the end of step S3), the temperature in the center of the formed lignocellulosic composite material can be at least 80°C, preferably between 80°C and 180°C, preferably between 90°C and 150°C, more preferably 95°C to 125°C.
[0122] Preferably, the temperature applied in step S3) is measured in the centre of the (three-dimensional) lignocellulosic composite material produced at the end of step S3).
[0123] In step S3), the compacted mixture (compacted mat) obtained after step S2) may be further compacted. Preferably, the pressure in step S3) is in the range of 0.1 to 10 MPa, preferably 0.5 to 8 MPa, and more preferably 1 to 6 MPa.
[0124] The temperature in the center of the lignocellulosic composite material can be measured according to known methods, in particular according to the method described by Meyer / Thoemen, Holz als Roh- und Werkstoff [European Journal of Wood and Wood Products]] (2007) 65, pp. 49-55, or Thoemen, 2010, “Vom Holzzum Werkstoff–grundlegende Untersuchungen zur Herstellung und Struktur von Holzwerkstoffen [From wood to materials-basic investigations for the preparation and the structure of wood-based materials]]”, ISBN 978-3-9523198-9-5, pp. 24 to 30 and 78 to 85. For the wireless measurement of the temperature, sensors such as the CONTI LOG sensor or the EASYlog sensor from Fagus-Grecon Greten GmbH & Co. KG can be used, which can be inserted into the mixture for producing the lignocellulose composite material, for example, during or after step S1). When a high frequency is applied during step S3), the temperature in the center of the lignocellulose composite material can be measured with a temperature sensor consisting of a Teflon-coated glass fiber with a gallium arsenide chip.
[0125] The application of heat in step S3) can be carried out by heat transfer from a heated surface, in particular from the hot surface of a press plate (in a single-opening press or a multi-daylight press) or a belt (in a double-belt press), and / or by high-frequency heating (application of a high-frequency electric field). For example, step S3) can be carried out in a conventional press (like a double-belt press CPS+ from Dieffenbacher GmbH Maschinen-und Anlagenbau or a double-belt press from Siempelkamp GmbH & Co. KG). After step S3), the lignocellulosic composite material ("board") can be cooled in a star cooler or more slowly by thermal stacking.
[0126] When the application of heat in step S3) is performed by heat transfer from hot surfaces, for example in a conventional hot press, the temperature of these surfaces is in the range of 80°C to 300°C, more preferably 120°C to 280°C, and even more preferably 150°C to 250°C.
[0127] In a preferred embodiment of the method of the present invention (or as described herein as a preferred method of the present invention), the heating in step S3) comprises preferably applying a high-frequency electric field to the mixture, preferably causing the binder to harden and bond the lignocellulosic particles so as to produce a lignocellulosic composite material (or layers of a multilayer lignocellulosic composite material).
[0128] As used herein, the term "high frequency electric field" is designated as and includes any kind of high frequency electric field or electromagnetic field, such as microwave radiation or high frequency electric field, which is generated after applying a high frequency alternating voltage at a plate capacitor between two capacitor plates. Suitable frequencies for high frequency electric fields are in the range of 100kHz to 30GHz, preferably 6MHz to 3GHz, more preferably 13MHz to 41MHz. Particularly suitable and preferred are corresponding domestically and internationally recognized frequencies, such as 13,56MHz, 27,12MHz, 40,68MHz, 2,45GHz, 5,80GHz, 24,12GHz, more preferably 13,56 and 27,12MHz. In the method of the present invention, the electric power for generating such a high frequency electric field is preferably in the range of 10 to 10000kWh, more preferably 100 to 5000kWh, most preferably 500 to 2000kWh.
[0129] Preferred is the process of the invention as described herein (or as described herein as preferred process of the invention), wherein the process for producing a lignocellulosic composite material comprises one, two, three, more than three or all of the following steps
[0130] - preparing, preferably by dispersing, a layer of the mixture provided or prepared in step S1), and compacting the layer in step S2),
[0131] - for the preparation of a multilayer lignocellulosic composite material comprising one or more lignocellulosic composite layers, at least a first and a second separate mixture are provided or prepared and the first and the second separate mixture are used for making a first layer and a second layer of the multilayer lignocellulosic composite material, wherein the first layer and the second layer are preferably in contact with each other and / or wherein the first and the second separate mixture have the same composition or have different compositions,
[0132] - for the preparation of a multilayer lignocellulosic composite material, two or more layers are prepared, preferably by dispersing individual layers on top of each other, each layer comprising lignocellulosic particles and a binder, wherein in the two or more layers the lignocellulosic particles and / or the binders are identical or different,
[0133] - preheating the mixture during or after compaction in step S2),
[0134] - heating in step S3) in such a way that during step S3) or at the end of step S3) the temperature in the centre of the formed lignocellulosic composite material may be at least 80°C, preferably between 80°C and 180°C, preferably between 90°C and 150°C, more preferably between 95°C and 125°C,
[0135] as well as
[0136] - In step S3), a pressure in the range of 1 to 10 MPa is applied to the compacted mixture from step S2).
[0137] According to the invention, any application of pressure (compaction) can be achieved in several stages.
[0138] According to a preferred aspect of the method of the present invention, the method for producing a lignocellulose composite material of the present invention comprises one, two, three or more preferred steps, which are specific embodiments of step S1), S2) or S3), or additional steps. Each of these preferred steps is optional and can be performed alone or in combination with one or more of the other preferred steps.
[0139] One of the preferred steps involves a step S1 of preparing the mixture comprising or consisting of the lignocellulosic particles and the binder composition. According to this preferred aspect, the lignocellulosic particles are blended with one or more or all components of the binder composition, or one or more or all components of the binder composition are sprayed onto the lignocellulosic particles. Specifically, the components of the binder composition are blended or sprayed onto the lignocellulosic particles simultaneously (e.g. in a mixture with each other) or sequentially, preferably sequentially, as further described and outlined above.
[0140] Another preferred step of the invention is the step of preparing a layer of the mixture provided or prepared in step S1), preferably by dispersing, and compacting the layer in step S2). Preparing the layer by dispersing is a preferred additional step for producing the lignocellulosic composite material.
[0141] According to a preferred aspect of the present invention, in order to prepare a multilayer lignocellulose composite material, at least a first and a second separate mixture is provided or prepared. The first and second separate mixtures are then used to make the first layer and the second layer of the multilayer lignocellulose composite material. Preferably, the first layer and the second layer are in contact with each other. According to this preferred aspect, the first and second separate mixtures have the same or different compositions, and even more preferably the first and second separate mixtures have different compositions. Therefore, different separate mixtures and / or layers of the prepared multilayer lignocellulose composite material are preferably different in specific properties such as density, color, etc. and / or they are different in their composition, wherein different compositions are obtained by using different binders, lignocellulose particles and / or other (additional) components such as plastics, fabrics, paint coatings, etc. (e.g., foreign matter derived from waste wood). The separate layers preferably (i) contain different binders and different lignocellulose particles, or (ii) contain the same binder but different lignocellulose particles, or (iii) contain the same binder and the same lignocellulose particles but different ratios.
[0142] According to the preferred method related to the technology of the present invention, the preparation of the multilayer lignocellulose composite material comprises the preparation of two, three or more layers, each layer comprising lignocellulose particles and a binder. Preferably, the lignocellulose particles and / or the binder in the two, three or more layers are the same or different, even more preferably, the lignocellulose particles are different and the binder is different.
[0143] In a preferred method of the present invention, the preparation of a single-layer lignocellulose composite material or a multi-layer lignocellulose composite material comprises the following steps:
[0144] - providing or preparing one, two or more than two mixtures comprising at least lignocellulosic particles according to the invention and a binder,
[0145] - dispersing the mixture / mixtures to obtain one, two or more than two layers, wherein the layer(s) form a mat,
[0146] - in a first compaction step during step S2), the single-layer or multi-layer mat is pre-compacted to obtain a pre-compacted mat, and thereafter
[0147] - In a second compaction step during step S3), the pre-compacted mat is compacted while applying heat and pressure.
[0148] The present invention also relates to a binder composition for the production of a lignocellulosic composite material, preferably as used and defined above in relation to the method according to the invention for producing a lignocellulosic composite material as described herein, or in relation to the method of the invention as described herein as preferred (or to a corresponding binder composition of the invention as described herein as preferred).
[0149] Generally, all aspects of the invention discussed herein in the context of the process for producing a lignocellulosic composite material according to the invention apply mutatis mutandis to the binder composition of the invention, and the use thereof, and vice versa.
[0150] Therefore, the present invention further relates to a binder composition or mixture for producing a lignocellulosic composite material, the binder composition or mixture comprising at least the following as components:
[0151] c1) one or more amino acid polymers having two or more primary amino groups, preferably comprising one or more polylysines (preferably as defined herein or as defined herein as preferred), and
[0152] c2) one or more polyaldehyde compounds selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups (preferably as defined herein or as defined herein as preferred).
[0153] Generally, all aspects of the invention discussed herein in the context of the process for producing a lignocellulosic composite material according to the invention and / or in the context of the binder composition of the invention apply mutatis mutandis to the binder composition of the invention and vice versa.
[0154] The present invention further relates to a lignocellulosic composite material obtainable or obtained according to the method according to the invention as described herein (or according to the method according to the invention as described herein as preferred), and / or to a building product comprising such a lignocellulosic composite material,
[0155] Wherein preferably, the lignocellulosic composite material is a lignocellulosic board selected from the group consisting of:
[0156] - High Density Fiberboard (HDF),
[0157] - Medium Density Fiberboard (MDF),
[0158] - Low-density fiberboard (LDF),
[0159] - wood fiber insulation boards,
[0160] -Oriented Strand Board (OSB),
[0161] - Particleboard, and
[0162] - natural fiberboard, preferably with fibers from the group consisting of sisal, jute, flax, coconut, kenaf, hemp, banana and mixtures thereof,
[0163] Wherein preferably the lignocellulosic board is
[0164] - single-layer wood cellulose board, or
[0165] -Multi-layer wood cellulose board,
[0166] A multi-layer lignocellulosic board having a core and having an upper surface layer and a lower surface layer is preferred.
[0167] Generally, all aspects of the invention discussed herein in the context of the method for producing a lignocellulosic composite material according to the invention, and / or the binder composition of the invention, and / or the use of the binder composition of the invention apply mutatis mutandis to the lignocellulosic composite material of the invention, and vice versa.
[0168] As used herein, the term "building product" designates a product used in construction such as decking, doors, windows, floors, panels, furniture or furniture parts. The building product of the present invention is preferably selected from the group consisting of furniture and furniture parts.
[0169] As used herein, the term "furniture" designates all kinds of furniture. In the context of the present invention, furniture is preferably selected from the group consisting of chairs, tables, desks, closets, beds and shelves.
[0170] As used herein, the term "building element" designates a lignocellulose composite product (e.g. a board, see above) constituting a part (element) of a building product (e.g. a furniture part). Such building element is preferably a furniture part, and more preferably such furniture part is selected from the group consisting of a shelf, a table top, a side panel or shelf or door of a cabinet and a side wall of a bed.
[0171] The lignocellulosic composite material, in particular the flooring, of the present invention, in particular if it is an element of the building product of the present invention, preferably comprises lignocellulosic particles selected from the group consisting of fibers, chips, strands, flakes, sawmill shavings and sawdust or mixtures thereof. These lignocellulosic particles are preferably derived from any type of lignocellulosic biomass, such as birch, beech, alder, pine, spruce, larch, eucalyptus, linden, poplar, ash, fir, tropical wood, sisal, jute, flax, coconut, kenaf, hemp, banana, straw, cotton stalks, bamboo, etc. or mixtures thereof.
[0172] The lignocellulosic composite material (preferably a board) of the present invention obtainable or obtained according to the method of the present invention is preferably a single-layer lignocellulosic board or a multi-layer lignocellulosic board, more preferably a single-layer lignocellulosic board. The multi-layer lignocellulosic board of the present invention is a board comprising at least two distinguishable (individual) layers. The multi-layer lignocellulosic board is preferably a board having at least one core layer and an upper surface layer and a lower surface layer. The total number of layers is then three or more. If the number of layers is four or more, one or more intermediate layers are present. Preferred is a three-layer board having a core layer, an upper surface layer and a lower surface layer. This is particularly suitable if the lignocellulosic composite material, preferably a board of the present invention is an element of the building product of the present invention.
[0173] Particularly preferred is the single-layer lignocellulosic board of the invention which is a medium density fiberboard (MDF) or a particleboard, even more preferably a medium density fiberboard (MDF), and corresponding building products comprising such a single-layer lignocellulosic board.
[0174] The present invention also relates to the use of a lignocellulosic composite material according to the invention as described herein (or to a corresponding lignocellulosic composite material as described herein as preferred) as a construction element in a building product, preferably selected from products for construction selected from the group consisting of decks, doors, windows, flooring, panels, furniture and furniture parts.
[0175] Generally, all aspects of the invention discussed herein in the context of the method for producing a lignocellulosic composite material according to the invention, and / or the binder composition of the invention, and / or the use of the binder composition of the invention, and / or the lignocellulosic composite material of the invention apply mutatis mutandis to the lignocellulosic composite material of the invention, and vice versa.
[0176] The present invention therefore also relates to a kit for producing a binder composition for the production of lignocellulosic composites, the kit comprising at least the following as spatially separated individual components:
[0177] k1) one or more amino acid polymers having two or more primary amino groups, preferably comprising one or more polylysines (preferably as defined herein or as defined herein as preferred), and
[0178] k2) one or more polyaldehyde compounds, preferably selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups (preferably as defined herein or as defined herein as preferred).
[0179] Therefore, the present invention further relates to the use of a binder composition according to the invention in a method for producing a lignocellulose composite material (or to the use of a corresponding binder composition according to the invention as described herein as preferred). Therefore, the present invention relates to the use of a binder composition in a method for producing a lignocellulose composite material, preferably in a method for producing a lignocellulose composite material according to the invention as described herein (or in a method of the invention as described herein as preferred), the binder composition comprising at least the following as components:
[0180] c1) one or more amino acid polymers having two or more primary amino groups, preferably comprising one or more polylysines (preferably as defined herein or as defined herein as preferred), and
[0181] c2) one or more polyaldehyde compounds, preferably selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups (preferably as defined herein or as defined herein as preferred).
[0182] Generally, all aspects of the invention discussed herein in the context of the method according to the invention for producing a lignocellulosic composite material, and / or the binder composition of the invention, and / or the use of the binder composition of the invention, and / or the lignocellulosic composite material of the invention, and / or the use of the lignocellulosic composite material of the invention apply mutatis mutandis to the kit of parts of the invention, and vice versa.
[0183] Examples :
[0184] The following examples are intended to further explain and illustrate the present invention without limiting the scope thereof.
[0185] A. Materials used
[0186] Glucose monohydrate (>99%), Sigma Aldrich, Spain
[0187] Fructose (>99%), Sigma-Aldrich, USA
[0188] Hexamethylenediamine (HMDA, >99%), Acros Organic
[0189] L-Lysine (98%), Sigma-Aldrich, Switzerland
[0190] L-lysine solution (50% in water), Archil Daniels Midland Animal Nutrition (ADManimal Nutrition), USA;
[0191] Carboxymethyl cellulose sodium salt (M w 250,000), Sigma-Aldrich 5-hydroxymethylfurfural (HMF), abcr GmbH, USA
[0192] Spruce wood chips (from the Institute of Wood Technology Dresden, Germany):
[0193] Spruce wood chips ("chips") are produced in a disc chipper. Spruce trunk segments from Germany (length 250 mm) are pressed with their long sides against rotating steel discs, into which radially and evenly distributed knife boxes are inserted, each consisting of radially arranged cutting knives and several scoring knives arranged at right angles thereto. The cutting knives separate the chips from the logs, and the scoring knives simultaneously limit the chip length. The produced chips are then collected in a silo and conveyed from there to a cross impact mill (with screens) for re-shredding according to the chip width. The re-shredded chips are then conveyed to a flash dryer and dried at approximately 120°C. The chips are then sieved into two useful fractions (B: ≤2.0 mm x 2.0 mm and >0.32 mm x 0.5 mm; C: ≤4.0 mm x 4,0 mm and >2.0 mm x 2.0 mm), a re-shredded coarse fraction (D: >4.0 mm x 4.0 mm) and a fine fraction (A: ≤0.32 mm x 0.5 mm). A mixture of 60 wt.-% of fraction B and 40 wt.-% of fraction C is used as chips for single-layer particleboards ("core chips").
[0194] B. Measurement values and measurement methods :
[0195] 1. Suppression time factor:
[0196] The pressing time factor is the pressing time (which is the time from closing to opening of the press) divided by the target thickness of the board. The target thickness refers to the board at the end of the pressing step (method step S3)) and is adjusted by the pressing conditions, i.e. by the distance between the top and bottom press plates, which is adjusted by inserting two steel spacers in the press (if a hot press is used) or by automatic distance control (if an HF press is used). Pressing time factor [sec / mm] = time from closing to opening of the press [sec]: target thickness of the pressed board [mm]. For example, when making a 10 mm particle board with a pressing time of 140 sec, a pressing time factor of 14 sec / mm is produced.
[0197] 2. Density of board:
[0198] The density of the board was measured according to EN 323:1993 and is reported as the arithmetic mean of ten 50 x 50 mm samples of the same board.
[0199] 3. Transverse tensile strength of the board ("internal bond"):
[0200] The transverse tensile strength ("internal bond") of the panels was determined according to EN 319:1993 and is reported as the arithmetic mean of ten 50 x 50 mm specimens of the same panel.
[0201] 4. Thickness expansion :
[0202] The thickness expansion of the panel after 24 h ("24h expansion") is determined according to EN 317:1993 and is reported as the arithmetic mean of ten 50 x 50 mm specimens of the same panel.
[0203] 5. Binder dosage:
[0204] The amount of binder in the examples according to the invention is reported as the total weight of the sum of the respective binder components amino acid polymer and polyaldehyde in wt.-%, based on the total dry weight of the wood particles (chips).
[0205] The binder amounts in the comparative examples are reported as the total weight of the sum of all binder components in wt.-%, based on the total dry weight of the wood particles (chips) (dry weight, which is the weight of the components without any water).
[0206] 6. Primary and secondary amino nitrogen content NC ps :
[0207] The primary and secondary amino nitrogen content is measured by potentiometric titration according to EN ISO 9702:1998.ps It means the weight of primary and secondary amino nitrogen per 100 g of amino acid polymer (given in wt.-%).
[0208] 7. Weight average molecular weight M w Determination
[0209] M w was determined by size exclusion chromatography under the following conditions:
[0210] Solvent and eluent: 0.1% (w / w) trifluoroacetate, 0.1 M NaCl in distilled water
[0211] Flow rate: 0.8ml / min
[0212] Injection volume: 100 μl
[0213] The samples were filtered with a Sartorius Minisart RC 25 (0,2 μm) filter.
[0214] Column material: Hydroxylated polymethacrylate (TSKgel G3000PWXL)
[0215] Column size: inner diameter 7.8mm, length 30cm
[0216] Column temperature: 35°C
[0217] Detector: DRI Agilent 1100UVGAT-LCD 503 [232nm]
[0218] Calibration with poly(2-vinylpyridine) standards (from Polymer Standards Service GmbH, Mainz, Germany) with molar masses ranging from 620 to 2,890,000 g / mol and pyridine (79 g / mol)
[0219] The upper limit of the integral is set to 29.01 mL
[0220] ·M w The calculations include lysine oligomers and polymers as well as monomeric lysine.
[0221] The residual lysine monomer content of the polylysine solution was determined by HPLC / MS analysis under the following conditions:
[0222] Injection volume: 10 μl
[0223] Eluent A: water + 0.02% formic acid
[0224] Eluent B: Water
[0225] ·gradient
[0226] time Eluent A Eluent B [min] [%] [%] 0 0 100 10 100 0 15 100 0 15.1 0 100 25 0 100
[0227] After 15 minutes, switch from eluent A to eluent B
[0228] Flow rate: 0.8ml / min
[0229] Column HPLC: Primesep C, 250 x 3.2 mm, 5 μm
[0230] Column temperature: 30℃
[0231] Calibrated with L-lysine solution in water
[0232] Mass spectrometer: Bruker Maxis (q-TOF)
[0233] ·MS conditions:
[0234] -Ionization mode: ESI, negatively charged
[0235] - Capillary: 3500V
[0236] -Sprayer: 1.4 bar
[0237] - Dry gas: 8l / min
[0238] - Temperature: 200℃
[0239] - Analyzed ions: 145.0983[MH] - ±0.005amu.
[0240] The residual lysine monomer content in the polylysine is given as wt.-% monomer, based on the total weight of the polylysine including the lysine monomer. For example, a 50 wt.-% polylysine-5 solution (see Table 1 below) having a lysine monomer content of 2.0 wt.-% contains 1 wt.-% lysine monomer and 49% wt.-% lysine polymer comprising at least 2 condensed lysine units.
[0241] 8. Determination of the ratio of ε-linkages to α-linkages in polylysine ("ratio ε / α"):
[0242] The ratio ε / α is obtained by 1 The H-NMR spectrum is determined by integrating the signals of -CH-NH2 and -CH-NH (α-linked) and -CH2-NH2 and -CH2-NH (ε-linked). 1 H, 15 The assignment was made using the N-HMBC (heteronuclear multiple bond correlation) experiment.
[0243] C. Preparation Example :
[0244] Preparation of different poly-lysine samples:
[0245] 2200 g of L-Lysine solution (50% in water, ADM) was heated in an oil bath (external temperature 140° C.) under stirring. Water was distilled off and the oil bath temperature was increased by 10° C. per hour until a temperature of 180° C. was reached. The reaction mixture was stirred for another hour at 180° C. (oil bath temperature), and the pressure was then slowly reduced to 200 mbar. After reaching the target pressure, distillation was continued for another time period t (specified in Table 1 below). The hot product was poured out of the reaction vessel, crushed after cooling and dissolved in water to obtain a 50 wt.-% solution. Polylysine samples "Polylysine 1" to "Polylysine 6" were produced according to this procedure. The reaction conditions applied in each case and certain measured parameters of the different polylysines are shown in Table 1 below.
[0246] In these examples, the lysine monomer contributes a certain amount of amino groups to the binder.
[0247] Residual lysine monomer content NC ps and M w Each was determined from this solution without any further purification. Residual lysine monomers were included in M w 's calculation.
[0248] Table 1 :Reaction conditions in synthesis and properties of different poly-lysine samples
[0249]
[0250] *The residual lysine monomer content is given in wt.-%, based on the total weight of the polylysine including the lysine monomer.
[0251] Comparative adhesive composition-1
[0252] 161 g of glucose monohydrate, 146 g of fructose and 161 g of L-lysine were mixed with 35 g of water and heated slowly (110° C. oil bath temperature). At 94° C., the mixture foamed and turned black. The reaction was stopped. The resulting reaction mixture contained solids and was not completely soluble in water.
[0253] Comparative adhesive composition-2
[0254] 286 g of glucose monohydrate, 260 g of fructose and 286 g of L-lysine were mixed with 174 g of water and heated slowly (100° C. oil bath temperature). At 90° C., the mixture foamed and turned dark brown. The oil bath was removed for 10 minutes. The reaction was heated again for 10 min to 100° C. until gas formation ceased. After cooling to RT, the mixture was filled into bottles and stored at 60° C. for 48 h.
[0255] Comparative adhesive composition-3
[0256] 235 g of hexamethylenediamine was dissolved in 730 g of water, 791 g of fructose and 853 g of glucose monohydrate were slowly added, and stirred at room temperature for one hour.
[0257] Comparative Binder Composition-4
[0258] 22.5 g of sodium carboxymethyl cellulose (NaCMC, M w About 250,000) was dissolved in 600 g of water. 67.5 g of hexamethylenediamine and 360 g of glucose monohydrate were slowly added and stirred at room temperature for 24 h.
[0259] Example 1 (according to the present invention)
[0260] Note: The term "resin-treated crumb" is used herein generally for a mixture of crumb with a binder composition and additionally added water.
[0261] In a mixer, a mixture of 499 g of polylysine-2 solution (50 wt.-% in water), 149 g of HMF solution (50 wt.-% HMF in water) and 100 g of water was sprayed onto 5.55 kg (5.40 kg dry weight plus 150 g water from the residual particle moisture content) of spruce core chips (moisture content 2.8%) while mixing. After adding the mixture, mixing was continued for 3 min. Some information about the components used for the preparation of the binder composition of this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0262] Comparative Example 2*
[0263] The contrast binder composition-1 is not uniform. It is impossible to spray the contrast binder composition-1 onto the chips. The attempt to mix the contrast binder composition-1 with the chips by pouring the binder composition onto the chips and stirring also failed to obtain a uniform mixture. However, this inhomogeneous mixture is used for pressing. Some information about the used components of the binder composition for the preparation of this example and about some parameters of the measurement of the resulting single-layer particleboard are shown in the following table 2.
[0264] Comparative Example 3*
[0265] In a mixer, a mixture of 404 g of comparative binder composition-2 and 244 g of water was sprayed onto 5.55 kg (5.40 kg dry weight plus 150 g of water from the residual particle moisture content) of spruce core chips (moisture content 2.8%) while mixing. 100 g of water was sprayed onto the mixture while mixing to adjust the final moisture of the resin-treated chips. After the addition of water, mixing was continued for 3 min. Some information about the components used for the binder composition used to prepare this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0266] Comparative Example 4*
[0267] In a mixer, a mixture of 469 g of comparative binder composition-3 and 179 g of water was sprayed onto 5.55 kg (5.40 kg dry weight plus 150 g of water from the residual particle moisture content) of spruce core chips (moisture content 2.8%) while mixing. 100 g of water was sprayed onto the mixture while mixing to adjust the final moisture of the resin-treated chips. After the addition of water, mixing was continued for 3 min. Some information about the components used for the binder composition used to prepare this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0268] Comparative Example 5*
[0269] In the mixer, 816 g of comparative binder composition-4 was sprayed onto 5.51 kg (5.40 kg dry weight plus 105 g water from the residual particle moisture content) of spruce core chips (moisture content 1.9%) while mixing. Thereafter, mixing was continued for 3 min. Some information about the components used for the preparation of the binder composition of this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0270] Comparative Example 6*
[0271] In a mixer, while mixing, a mixture of 499 g of polylysine-2 solution (50 wt.-% in water), 164 g of glucose monohydrate (equivalent to 149 g of glucose) and 285 g of water was sprayed onto 5.51 kg (5.40 kg dry weight plus 105 g of water from the residual particle moisture content) of spruce core chips (moisture content 1.9%). After adding the mixture, mixing was continued for 3 min. Some information about the components used for the preparation of the binder composition of this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0272] Pressing of resin-treated chips into particleboard (According to Example 1 of the invention and Comparative Examples 2* to 6*)
[0273] Immediately after resin treatment, 600 g of the crumb / binder mixture was spread into a 30 x 30 cm mold and pre-compacted (0.4 N / mm 2 The pre-compacted chip mat thus obtained was subsequently removed from the mold, transferred to a hot press and pressed to a thickness of 10 mm to obtain a particleboard (pressing plate temperature 210° C., maximum pressure 4 N / mm 2 , pressing time 140 sec). Some information about the components used for preparing the binder composition of this example and about certain parameters measured for the resulting single-layer particleboard is shown in Table 2 below.
[0274] Table 2 : Single-layer particleboard, 10 mm, with different binder compositions according to the invention and comparative examples, binder amount 6 wt.-% (solid / dry wood), pressing time factor 14 sec / mm
[0275]
[0276] *Comparative Examples
[0277] 1) Weight ratio
[0278] np = production of particleboard was not possible because comparative binder-1 was not homogeneous and could not be evenly distributed on the chips;
[0279] nq = cannot be quantified because the test sample broke into pieces within 24 h;
[0280] "No board" means that the resulting material after pressing is not an undamaged particle board and shows cracking, splitting and / or popping.
[0281] The above results show that the binder according to the invention based on polylysine and polyaldehyde compounds gives boards with improved properties when compared to boards prepared by a method not according to the invention (e.g. prepared with a comparative binder based on amine and sugar compounds). Boards prepared by a method not according to the invention but with a binder comprising polylysine and a reducing sugar (here: glucose, see Example 6 in Table 2 above) show lower internal bond strength and higher 24h swelling values than boards prepared by a method according to the invention (see Example 1 in Table 2 above).
[0282] The following examples 7 to 11 (all according to the invention) relate to the manufacture of single-layer particleboards with polylysine-2 and HMF and different modes of application. Some information about the components used for the preparation of the binder compositions of examples 7 to 11 and about certain parameters measured for the resulting single-layer particleboards is shown in Table 3 below.
[0283] Example 7: Applying the binder composition to wood chips alone
[0284] In the mixer, 454 g of polylysine-2 solution (50 wt.-% in water) were sprayed onto 5.55 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) while mixing. Subsequently, 194 g of HMF solution (50 wt.-% HMF in water) were sprayed onto the mixture while mixing. Finally, 100 g of water were sprayed onto the mixture while mixing to adjust the final moisture of the resin-treated chips.
[0285] Example 8: Application of Binder System Alone to Wood Chips
[0286] In the mixer, 194 g of HMF solution (50 wt.-% HMF in water) was sprayed onto 5.55 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) while mixing. Subsequently, 454 g of polylysine-2 solution (50 wt.-% in water) was sprayed onto the mixture. Finally, 100 g of water was sprayed onto the mixture while mixing to adjust the final moisture of the resin-treated chips. After the addition of water, mixing was continued for 3 min.
[0287] Examples 9 to 11: Mixing and applying the binder composition to wood chips
[0288] 2.00 kg of polylysine-2 solution (50 wt.-% in water) and 857 g of HMF solution (50 wt.-% HMF in water) were mixed by stirring at 22° C. for 1 min. In the mixer, while mixing, 648 g of this mixture were sprayed onto 5.55 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) either immediately after mixing or after a waiting time as given in Table 3 (storage in a closed box at 22° C.). Subsequently, 100 g of water were sprayed onto the mixture while mixing to adjust the final moisture of the resin-treated chips. After the addition of the water, mixing was continued for 3 min.
[0289] Examples 7 to 11: Pressing of resin treated chips into particleboard
[0290] Immediately after resin treatment, 600 g of the crumb / binder mixture was spread into a 30 x 30 cm mold and pre-compacted (0.4 N / mm 2 The pre-compacted chip mat thus obtained was subsequently removed from the mold, transferred to a hot press and pressed to a thickness of 10 mm to obtain a particleboard (pressing plate temperature 210° C., maximum pressure 4 N / mm 2 , pressing time 140sec).
[0291] Table 3 : Single-layer particleboard, 10 mm, binder content (components A+B): 6 wt.-% (solid / dry wood), pressing time factor = 14 sec / mm
[0292]
[0293] Waiting time = time between the end of mixing of polylysine-2 and HMF and the start of spraying the binder composition mixture onto the chips, PL-2 = polylysine-2 solution (50 wt.-% in water), see above for preparation;
[0294] nd = not determined
[0295] Single = single application (first poly-lysine-2, second HMF)
[0296] Single* = single application (first HMF, second poly-lysine-2)
[0297] Mix = Apply a mixture of polylysine-2 and HMF
[0298] The results in Table 3 above show that a mixture of an amino acid polymer (e.g. polylysine) and a polyaldehyde (e.g. HMF) can be used, or both components can be applied to the crumbs separately, but the use of a mixture is preferred. In addition, the system allows for a long waiting time between the preparation of the mixture and its application to the crumbs.
[0299] Examples 12* to 18: Preparation of Resin-treated Chips
[0300] In a mixer, a mixture of 499 g of L-lysine solution (50 wt.-% in water, comparative example 12*) or polylysine solution (50 wt.-% in water, polylysine-1 to polylysine-6, examples 13 to 18), 149 g of HMF solution (50 wt.-% HMF in water) and 100 g of water was sprayed onto 5.54 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) while mixing. After adding the mixture, mixing was continued for 3 min.
[0301] Examples 12* to 18: Pressing of resin treated chips into particleboard
[0302] Immediately after resin treatment, 600 g of the crumb / binder mixture was spread into a 30 x 30 cm mold and pre-compacted (0.4 N / mm 2 The pre-compacted chip mat thus obtained was subsequently removed from the mold, transferred to a hot press and pressed to a thickness of 10 mm to obtain a particleboard (pressing plate temperature 210° C., maximum pressure 4 N / mm 2 , pressing time 140sec).
[0303] Certain information about the components used for the preparation of the binder compositions of Example 12 (for comparison) and Examples 13 to 18 (all according to the invention) as well as certain parameters measured on the resulting single-layer particleboards is shown in Table 4 below.
[0304] Table 4 : Single-layer particleboard, 10 mm, binder dosage (A+B): 6 wt.-% (solid / dry wood), mixed application, pressing time factor 14 sec / mm
[0305]
[0306] *Comparative example,
[0307] 1) Amino acid polymer or comparison component
[0308] 2) M of amino acid polymer w is measured by size exclusion chromatography.
[0309] “PL-1” to “PL-6”: Solutions of “Polylysine-1” to “Polylysine 6” (50 wt.-% in water) (for preparation and properties see description above and Table 1).
[0310] The above results in Table 4 show that amino acid polymers (polylysine) of different weight average molecular weights work well, while amino acid (lysine) monomers do not work. The weight average molecular weight of the amino acid polymer (polylysine) has an optimal range of about 3000 g / mol.
[0311] The following examples 19 to 21 (all according to the invention) relate to the manufacture of single-layer particleboards with polylysine-2 and different weights of HMF. Some information about the components used for the preparation of the binder compositions of Examples 19 to 21 and about certain parameters measured for the resulting single-layer particleboards is shown in Tables 5 and 6 below.
[0312] In a mixer, a mixture of x1 amount of polylysine-2 solution (50 wt.-% in water), y1 amount of HMF solution (50 wt.-% HMF in water) and 100 g of water was sprayed onto 5.55 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) while mixing. After adding the mixture, mixing was continued for 3 min.
[0313] Table 5 : x1 amount of poly-lysine-2 solution and y1 amount of HMF solution
[0314]
[0315] Examples 19 to 21: Pressing of resin treated chips into particleboard
[0316] Immediately after resin treatment, 600 g of the crumb / binder mixture was spread into a 30 x 30 cm mold and pre-compacted (0.4 N / mm 2 The pre-compacted chip mat thus obtained was subsequently removed from the mold, transferred to a hot press and pressed to a thickness of 10 mm to obtain a particleboard (pressing plate temperature 210° C., maximum pressure 4 N / mm 2 , pressing time 140sec).
[0317] Table 6 : Single-layer particleboard, 10 mm, binder dosage (component A+B): 6 wt.-% (solid / dry wood), mixed application, pressing time factor 14 sec / mm
[0318]
[0319] 1) Amino acid polymer
[0320] The above results in Table 6 show that the ratio of amino acid polymer (polylysine) to polyaldehyde (HMF) can vary. A ratio of less than 70:30, but preferably not less than 50:50 is preferred.
[0321] The following examples 22 to 27 (all according to the invention) relate to the manufacture of single-layer particleboards (by pressing in a high-frequency press) with polylysine-2 and different weights of HMF. Some information about the components used for the preparation of the binder compositions of Examples 22 to 27 and about certain parameters measured for the resulting single-layer particleboards is shown in Tables 7 and 8 below.
[0322] In a mixer, a mixture of x2 amount of polylysine-2 solution (50 wt.-% in water), y2 amount of HMF solution (50 wt.-% HMF in water) and 100 g of water was sprayed onto 5.55 kg (5.40 kg dry weight) of spruce core chips (moisture content 2.8%) while mixing. After adding the mixture, mixing was continued for 3 min.
[0323] Table 7 : x2 amount of poly-lysine-2 solution and y2 amount of HMF solution
[0324]
[0325] Examples 22 to 27: Pressing of resin treated chips into particleboard in a high frequency press
[0326] Immediately after resin treatment, 600 g of the resin treated crumbs were spread into a 30 x 30 cm mold and pre-compacted (0.4 N / mm 2 ). Subsequently, the pre-compressed crumb pad thus obtained is taken out from the mold. In order to monitor the temperature, a temperature sensor (GaAs chip) is introduced into the center of the pre-compacted crumb pad. Then a non-woven separator (separator) is provided to the upper and lower sides of the pre-compacted crumb pad. The pre-compacted crumb pad is inserted into the HLOP 170 press from Hoefer Presstechnik GmbH, whereby birch plywood (thickness 6mm) is placed between the non-woven separator and the press plate on each side of the pad. The pre-compacted crumb pad is then compacted to a thickness of 10mm in the press over a period of 2s, and then heated by applying a high-frequency electric field (27.12MHz, anode current 2.5A) while the press remains closed. When the target temperature of 130°C is reached at the center of the pressed pad (reaching 130°C after 75±15sec), the press is opened.
[0327] Table 8 : Single-layer particleboard (high-frequency press), 10 mm, binder amount (component A+B): 6 wt.-% (solid / dry wood), mixed application
[0328]
[0329] 1) Amino acid polymer
Claims
1. A method for producing a lignocellulosic composite material comprising one or more lignocellulosic composite material layers, the method comprising at least the following steps: S1) providing or preparing a mixture comprising at least: -Lignocellulosic particles as well as - A binder composition comprising at least the following as components: c1) one or more amino acid polymers having two or more primary amino groups, and c2) one or more polyaldehyde compounds, S2) compacting the mixture from step S1) to obtain a compacted mixture, as well as S3) applying heat and optionally pressure to the compacted mixture from step S2) such that the binder of the binder composition hardens and produces a lignocellulosic composite material.
2. The method according to claim 1, comprising at least the following steps: S1) providing or preparing a mixture comprising at least: -Lignocellulosic particles as well as - A binder composition comprising at least the following as components: c1) one or more amino acid polymers having two or more primary amino groups, preferably comprising one or more polylysine, and c2) one or more polyaldehyde compounds selected from the group consisting of compounds having two or more aldehyde groups and compounds having tautomers containing two or more aldehyde groups; S2) compacting the mixture from step S1) to obtain a compacted mixture, as well as S3) applying heat and optionally pressure to the compacted mixture from step S2) such that the binder of the binder composition hardens and produces a lignocellulosic composite material.
3. A method according to any one of the preceding claims, wherein: The one or more amino acid polymers of component c1) of the binder composition comprise one or more polylysines, Preferably, the one or more polylysine - having a weight average molecular weight M of ≥800 g / mol, preferably ≥1000 g / mol, more preferably ≥1150 g / mol, even more preferably ≥1500 g / mol w ; and / or - having a weight average molecular weight M of ≤10000 g / mol, preferably ≤8000 g / mol, more preferably ≤5000 g / mol, still more preferably ≤4000 g / mol w ; and / or -With a temperature of 800g / mol≤M w ≤10000 g / mol, preferably 1000 g / mol≤M w ≤8000g / mol, more preferably 1500g / mol≤M w ≤5000 g / mol, and still more preferably 1800 g / mol≤M w Weight average molecular weight M within the range of ≤4000g / mol w ; and / or - comprises at least 85 wt.-%, preferably at least 95 wt.-%, more preferably at least 99 wt.-% and still even more preferably 100 wt.-% of lysine monomers as monomers integrated in its polymer structure.
4. A method according to any one of the preceding claims, wherein: The binder composition is one or one of the multiple polyaldehyde compounds of component c2), or all of the multiple polyaldehyde compounds are selected from the group consisting of oxidized starch, glyoxal, dialdehyde cellulose, malondialdehyde, succindialdehyde, glutaraldehyde, adipaldehyde, furan-2,5-dicarboxaldehyde, 5-(hydroxymethyl)furan-2-carboxaldehyde (HMF), 3-hydroxy-2-oxo-propionaldehyde, and mixtures thereof, Preferably selected from the group consisting of glyoxal, furan-2,5-dicarbaldehyde, 5-(hydroxymethyl)furan-2-carbaldehyde, and mixtures thereof; More preferably, one or at least one of the plurality of polyaldehyde compounds is 5-(hydroxymethyl)furan-2-carbaldehyde.
5. A method according to any one of the preceding claims, wherein: The mixture further comprises one or more α-hydroxycarbonyl compounds, which are preferably selected from the group consisting of glycolaldehyde, glyceraldehyde, 1,3-dihydroxyacetone, hydroxyacetone, arabinose, xylose, glucose, mannose, fructose, sucrose, and mixtures thereof.
6. A method according to any one of the preceding claims, wherein: - the ratio of the total weight of (i) the one or more amino acid polymers of the binder composition being component c1) to the total weight of (ii) the one or more polyaldehyde compounds of the binder composition being component c2) is in the range of 60:40 to 95:5, preferably 65:35 to 90:10, and more preferably 70:30 to 90:10, and / or - The molar ratio of (i) primary amino groups provided by the one or more amino acid polymers of the binder composition being component c1) to (ii) aldehyde groups provided by the one or more polyaldehyde compounds of the binder composition being component c2) is in the range of 0.1 to 1.2, preferably 0.2 to 1.0, and more preferably 0.3 to 0.
8.
7. A method according to any one of the preceding claims, wherein: The binder composition provided or prepared in step S1) further comprises a carrier liquid, preferably water, Among them, preferably - component c1) the one or more amino acid polymers are present in the binder composition in a total amount ranging from ≥ 20 wt.-% to ≤ 50 wt.-%, preferably from ≥ 25 wt.-% to ≤ 45 wt.-%, and more preferably from ≥ 25 wt.-% to ≤ 40 wt.-%, relative to the total weight of components c1) to c2) and the carrier liquid; and / or - component c2) the one or more polyaldehyde compounds are present in the binder composition in a total amount in the range of ≥3 wt.-% to ≤20 wt.-%, preferably ≥5 wt.-% to ≤15 wt.-%, and more preferably ≥7 wt.-% to ≤12 wt.-%, relative to the total weight of components c1) to c2) and the carrier liquid; and / or The pH value of the binder composition is in the range of 10-14, preferably 11-14, more preferably 12-14.
8. A method according to any one of the preceding claims, wherein: In the mixture provided or prepared in step S1) of the method, The total amount of component c1) of the binder composition, the one or more amino acid polymers, and component c2) of the binder composition, the one or more polyaldehyde compounds The total amount of the lignocellulosic particles in oven-dried state relative to the mixture is in the range of ≥3 to ≤8 wt.-%, preferably ≥3.5 to ≤7.5 wt.-% and more preferably ≥4 to ≤6.5 wt.-%.
9. A method according to any one of the preceding claims, wherein: The mixture in step S1) is prepared by providing or preparing in a first step S1-1) the binder composition comprising at least components c1) and c2) and preferably water, and in a second step S1-2), contacting the binder composition provided or prepared in step S1-1) with the lignocellulosic particles, preferably spraying the binder composition onto the lignocellulosic particles.
10. A method according to any one of the preceding claims, wherein: The lignocellulosic composite material is a lignocellulosic board selected from the group consisting of: - High-density fiberboard (HDF); - Medium density fiberboard (MDF); - Low-density fiberboard (LDF); - wood fiber insulation boards; - Oriented Strand Board (OSB); - Particleboard; as well as - natural fiberboard, preferably with fibers from the group consisting of sisal, jute, flax, coconut, kenaf, hemp, banana and mixtures thereof; The wood cellulose board is - single-layer wood cellulose board, or -Multi-layer wood cellulose board, A multi-layer lignocellulosic board having a core layer and having an upper surface layer and a lower surface layer is preferred.
11. A method according to any one of the preceding claims, wherein: The method for producing a lignocellulosic composite material comprises one, two, three, more than three, or all of the following steps: - preparing, preferably by dispersing, a layer of the mixture provided or prepared in step S1), and compacting the layer in step S2), - for the preparation of a multilayer lignocellulosic composite material comprising one or more lignocellulosic composite layers, at least a first and a second separate mixture are provided or prepared and the first and the second separate mixture are used for making a first layer and a second layer of the multilayer lignocellulosic composite material, wherein the first layer and the second layer are preferably in contact with each other and / or wherein the first and the second separate mixture have the same composition or have different compositions, - for the preparation of a multilayer lignocellulosic composite material, two or more layers are prepared, preferably by dispersing individual layers on top of each other, each layer comprising lignocellulosic particles and a binder, wherein in the two or more layers the lignocellulosic particles and / or the binders are identical or different, - in step S2), the mixture is compacted in one or more two stages, - preheating the mixture during or after compaction in step S2), - heating in step S3) in such a way that during step 3) or at the end of step S3) the temperature in the centre of the formed lignocellulosic composite material may be at least 80°C, preferably between 80°C and 180°C, preferably between 90°C and 150°C, more preferably between 95°C and 125°C, as well as - In step S3), a pressure in the range of 0.1 to 10 MPa is applied to the compacted mixture from step S2).
12. The method according to claim 11, wherein: The heating in step S3) comprises applying a high frequency electric field.
13. A binder composition or mixture for producing a lignocellulosic composite material, the binder composition or mixture comprising at least the following as components: c1) one or more amino acid polymers having two or more primary amino groups, and c2) one or more polyaldehyde compounds Preferably wherein the binder composition is as defined in any one of claims 2 to 8.
14. A lignocellulosic composite material obtainable or obtained according to the method of any one of claims 1 to 12, or a building product comprising such a lignocellulosic composite material, Preferably, the lignocellulose composite material is a lignocellulose board selected from the group consisting of -High Density Fiberboard (HDF) -Medium Density Fiberboard (MDF) -Low Density Fiberboard (LDF) -Wood fiber insulation board -Oriented Strand Board (OSB) - Particleboard, and - natural fiberboard, preferably with fibers from the group consisting of sisal, jute, flax, coconut, kenaf, hemp, banana and mixtures thereof, - wherein preferably the lignocellulosic board is - single-layer wood cellulose board, or -Multi-layer wood cellulose board, A multi-layer lignocellulosic board having a core and having an upper surface layer and a lower surface layer is preferred.
15. Use of the lignocellulosic composite material according to claim 14 as a construction element in a building product, The building product is preferably selected from products for construction selected from the group consisting of decks, doors, windows, floors, panels, furniture and furniture parts.
16. A kit for producing a binder composition for the production of lignocellulosic composite materials, the kit comprising at least the following as spatially separated individual components: k1) one or more amino acid polymers having two or more primary amino groups, preferably wherein the amino acid polymer is as defined in claim 2 or 3, and k2) one or more polyaldehyde compounds, preferably wherein the polyaldehyde compound is as defined in claim 2 or 4.
17. Use of a binder composition in a method for producing a lignocellulosic composite material, the binder composition comprising at least the following as components: c1) one or more amino acid polymers having two or more primary amino groups, and c2) one or more polyaldehyde compounds, Preferably wherein the binder composition is as defined in any one of claims 2 to 8.
Citation Information
Patent Citations
Binder composition, article, and method for manufacturing article
EP3611225A2
Durable thermosets from reducing sugars and primary polyamines
US20110262648A1
binders
WO2015177114A1
Resin-impregnated fibrous material in the form of a sheet or a web
WO2022008671A1
Cellulosic composite
US20110045966A1